2020
DOI: 10.1039/d0py01061h
|View full text |Cite
|
Sign up to set email alerts
|

Boosting or moderating surface-initiated Cu(0)-mediated controlled radical polymerization with external additives

Abstract: Surface-initiated Cu(0)-mediated controlled radical polymerization (SI-CuCRP) has been proved as a powerful method for the fabrication of polymer brushes with various architectures. A key factor in SI-CuCRP process is the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…These results agree with previous studies that reported linearly increasing brush thickness with d for gradient brushes, prepared via tilting the copper plate relative to the substrate, using several other monomers. 37,38,47,62 Increasing brush thickness with d is likely due to lower concentrations of radicals and activator species at the substrate surface at larger d, resulting in lower rates of termination reactions. 37,47 Increasing d to 1000 μm or higher resulted in lower brush thickness or no growth after 60 min of polymerization time (data not shown), likely due to higher concentrations of dissolved oxygen that delayed or inhibited brush growth.…”
Section: Psbma Brush Grafting From Si Wafer Substratesmentioning
confidence: 99%
“…These results agree with previous studies that reported linearly increasing brush thickness with d for gradient brushes, prepared via tilting the copper plate relative to the substrate, using several other monomers. 37,38,47,62 Increasing brush thickness with d is likely due to lower concentrations of radicals and activator species at the substrate surface at larger d, resulting in lower rates of termination reactions. 37,47 Increasing d to 1000 μm or higher resulted in lower brush thickness or no growth after 60 min of polymerization time (data not shown), likely due to higher concentrations of dissolved oxygen that delayed or inhibited brush growth.…”
Section: Psbma Brush Grafting From Si Wafer Substratesmentioning
confidence: 99%
“…Grafting polymer brushes with targeted construction and functionality have been intensively used to realize surface modifications and possessed potentials in biolubrication, antifouling, , biomedical, and energy engineering. An appealing strategy for preparing diverse polymer brushes is surface-initiated atom transfer radical polymerization (SI-ATRP or SI-CRP), , including activators regenerated by electron transfer (ARGET) ATRP, photo-ATRP, , electrochemically mediated ATRP (eATRP), and supplemental activator and reducing agent (SARA) ATRP. The last mentioned technology deserves special attention because it allows precise control of the chemical composition, structure, and thickness of polymer brushes. So far, the transition metal catalysts have been extended to Cu, ,, Fe, ,, Zn, and Sn since surface-initiated zerovalent metal-mediated controlled radical polymerization (SI-Mt 0 CRP) was proposed. Among them, SI-Fe 0 ATRP was considered one of the best choices for “green” reactions because of the low toxicity, cost-effectiveness, and biocompatibility of iron-based catalysts. , However, the classical iron-based catalytic systems normally show limited monomer suitability, slow polymerization rate, and weak controllability over the polymerization. , …”
Section: Introductionmentioning
confidence: 99%
“…However, SI-CRP strategies have long been suffering from poor polymerization efficiency, rigorous inert atmosphere, and vast consumption of transition-metal halide catalysts and monomer solution . To overcome these obstacles, a series of innovative and powerful techniques have been explored, triggered by various external stimuli such as electrochemistry, the addition of a reducing agent, , photochemistry, enzymes, microbial metabolism, and the use of zerovalent metals. , Among these, using zerovalent metals in SI-CRP is not brand new as it has been widely used in traditional supplemental activator and reducing agent atom-transfer radical polymerization (SARA ATRP) . In 2015, our group first reported the surface-initiated Cu(0)-mediated CRP (SI-Cu 0 CRP), , which succinctly used a copper plate as the catalyst but no additional Cu I/II species, coupled with ligand and monomer mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, our group first reported the surface-initiated Cu(0)-mediated CRP (SI-Cu 0 CRP), , which succinctly used a copper plate as the catalyst but no additional Cu I/II species, coupled with ligand and monomer mixtures. Due to the confined geometry of the setup and the proximity of the metal plate to the initiator SAM, the SI-Cu 0 CRP was found to be oxygen-tolerant, with marvelous reinitiation efficiencies and grafting densities. , Functional polymer brushes with well-defined chemical configurations, thicknesses, densities, and architectures have been easily achieved over large areas while consuming only microliter volumes of monomer solution. In addition, SI-Mt 0 CRP is well compatible with other emerging technologies, including “on water” reaction, galvanic replacement, lithography, and capillary microfluidics, which significantly broaden the universality of this technique.…”
Section: Introductionmentioning
confidence: 99%